Extending the South African child support grant: a cost-effectiveness analysis of implementing a pregnancy support grant - Moolla, Aisha (My University, 2022)
Introduction: The child support grant (CSG) was introduced to reduce child poverty in South Africa. However, it fails to address the negative health consequences of maternal poverty during pregnancy. This study aims to determine whether a pregnancy support grant (PSG), through the extension of the CSG, would be costeffective. Methods and materials: Decision tree analytical modelling was used to determine the costs and benefits of the intervention over a 2-year time horizon. An ingredientsbased approach to costing was used from a governmental perspective. Benefits were presented as disability-adjusted life years (DALYs) averted. Health states included antenatal care, stillbirth, preterm birth, low birth weight, small-for-gestational age, infant death, respiratory distress syndrome, neonatal hypoglycaemia, chronic lung disease, and motor impairment. Results: The PSG was found to reduce costs by ZAR31,200.00 per person. An incremental cost-effectiveness ratio of -ZAR233,000.00 per DALY averted was estimated, which was below the ZAR38,500.00 threshold. Discussion: The results are supported by current literature, which shows that income support interventions during pregnancy are cost-effective. The major limitation of this study is the use of secondary data from published literature. This may under- or overestimate parameters. However, parameters were varied in the sensitivity analysis. Conclusion: The results indicate that the PSG is highly cost-effective. Recommendations: The PSG should be implemented by government using an intergovernmental co-funding approach.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Public Health to the Faculty of Health Sciences, School of Public Health, University of Witwatersrand, Johannesburg, 2022